Trial in absentia and the modern international criminal procedure - A. B. Mezyaev (Московский журнал международного права)
INTRODUCTION. The article discusses the theoretical and practical problems of conducting trials in the absence of the accused (in absentia) in international criminal courts and tribunals.MATERIALS AND METHODS. The article is based on international human rights treaties that regulate the rights of the accused in criminal proceedings, the statutory and procedural documents of these courts, and the practice of interpreting and applying the right of the accused to be present at the trial.RESEARCH RESULTS. International human rights treaties establish the minimum rights of the accused in criminal proceedings. Among these rights is the right of the accused to be present at the trial. However, the practice of interpreting this right by the relevant conventional international bodies and international criminal courts and tribunals imposes significant limitations. A number of such restrictions appear to be both reasonable and justified. However, in many cases the restrictions are arbitrary and their justification is legally flawed.DISCUSSION AND CONCLUSIONS. Universal and a number of regional international human rights treaties, in particular, the International Covenant on Civil and Political Rights of 1966 contain norms that are binding not only for states in their application of national law, but also establish general human rights standards in international law. Due to this circumstance, the provisions of such treaties bind any institutions operating directly in the system of international law, in particular, international criminal courts and tribunals. Thus, international criminal courts and tribunals are bound by the provisions of these treaties, not only in terms of their implementation, but also in terms of their interpretation. The practice of these courts demonstrates a very inconsistent application and not always convincing interpretation of the rights of the accused in general and the right to be tried in his presence. Currently, this practice is trying to change the previously formed trend towards increasingly severe restrictions on exceptions to the right of the accused to be tried in his presence.